In vitro and in vivo antiplasmodial activity of hydroethanolic bark extract of Bridelia atroviridis müll. Arg. (Euphorbiaceae) and lc-ms-based phytochemical analysis. (10th February 2021) - Djouwoug, Clarice Noussi; Gounoue, Raceline Kamkumo; Ngueguim, Florence Tsofack; NankapTsakem, Jaures Marius; Gouni, Clemence Donfack; Kandeda, Antoine Cavaye; Ngouela, Silvere; Lenta, Bruno Ndjakou; Sewald, Nobert; Fekam, Fabrice Boyom; Dimo, Théophile
Abstract: Ethnopharmacological relevance: Malaria is a life-threatening health problem worldwide and treatment remains a major challenge. Natural products from medicinal plants are credible sources for better anti-malarial drugs. Aim of the study: This study aimed at assessing the in vitro and in vivo antiplasmodial activities of the hydroethanolic extract of Bridelia atroviridis bark. Materials and methods: The phytochemical characterization of Bridelia atroviridis extract was carried out by High-Performance Liquid Chromatography-Mass spectrometry (HPLC-MS). The cytotoxicity test on Vero cells was carried out using the resazurin-based assay while the in vitro antiplasmodial activity was determined on Plasmodium falciparum (Dd2 strain, chloroquine resistant) using the SYBR green I-based fluorescence assay. The in vivo assay was performed on Plasmodium berghei- infected rats daily treated for 5 days with distilled water (10 mL/kg) for malaria control, 25 mg/kg of chloroquine sulfate for positive control and 50, 100 and 200 mg/kg of B. atroviridis extract for the three test groups. Parasitaemia was daily monitored using 10% giemsa-staining thin blood smears. At the end of the treatment, animals were sacrificed, blood was collected for hematological and biochemical analysis while organs were removed for biochemical and histopathological analyses. Results: The HPLC-MS analysis data of B. atroviridis revealed the presence of bridelionoside D, isomyricitrin, corilagin, myricetin and 5 others compounds not yet identified. Bridelia atroviridis exhibited good in vitro antiplasmodial activity with the IC50 evaluated at 8.08 μg/mL and low cytotoxicity with the median cytotoxic concentration (CC50 ) higher than 100 μg/mL . B. atroviridis extract significantly reduced the parasitemia (p < 0.05) with an effective dose-50 (ED-50) of 89 mg/kg. B. atroviridis also prevented anemia, leukocytosis and liver and kidneys impairment by decrease of transaminases, ALP, creatinine, uric acid, and triglycerides concentrations. As well, B. atroviridis extract decreased some pro-inflammatory cytokines (TNF-α, IL-1β, IL-6) levels and significantly improved the anti-inflammatory status (P < 0.01) of infected animals marked by a decrease of IL-10 concentration. These results were further confirmed by the improved of antioxidant status and the quasi-normal microarchitecture of the liver, kidneys and spleen in test groups. Overall, the hydroethanolic bark extract of Bridelia atroviridis demonstrated antimalarial property and justified its use in traditional medicine to manage malaria disease. Graphical abstract: Image 1